Une intervention en clinique de l’activité à visée transformative : apports pour la conception d’une formation de formatrices et formateurs libanais - Sylvie Moussay; Suzanne Abdul-Reda Abourjeili (Recherches en Éducation)
Historically rooted in the culture of successive reforms in the field of education, the issue of continuing training for Lebanese trainers remains central despite the efforts made by the Ministry of Education and Teaching. Inscribed in this context of a desire for change and in response to an order from the Lebanese Center for Educational Research and Development, the activity’s intervention-clinical research aimed at developing the activity of the trainers of teachers through the mediation of activity analysis tools. The analysis of self-confrontation interview data and collective exchanges gives rise to tangible results on the development of the activity of trainers and the concrete transformations taken up during exchanges between peers and managers of training centers. The results of the intervention bring into discussion the question of the use of activity analysis for the design of training for trainers.